An investigation of real estate as an asset class for pension funds portfolio investment in Botswana - Mapira, Fungisai (Department of Construction Economics and Management, 2025)
Pension funds hold the largest share in global capital markets and prudently invest in diverse income-generating assets to meet their current and future liabilities. Real estate is held in pension fund mixed asset portfolios to match long-term liabilities. The viability of real estate as an investment asset is defined by its qualities of hedging against inflation, portfolio diversification, risk reduction, capital appreciation and steady income flows. The current pension fund regulatory framework in Botswana allows for a minimum of 30% of funds to be invested locally where real estate holds a 2% investment stake. The study seeks to investigate the viability of real estate as an asset class for pension funds in Botswana and ascertain factors which influence its allocation in their portfolios. A qualitative multiple case study approach was used to gather data through semistructured interviews of five key stakeholders from five Botswana pension funds. Interviewees were asked questions centered around their Organisations' investment strategies and interest towards real estate assets. Pattern matching was used for data analysis by matching theoretical patterns to empirical findings. The findings revealed that real estate is a viable asset class for pension funds in Botswana and is incorporated in their investment strategies. In addition, there is increased investment appetite towards real estate though the local market offers limited options resulting in high and expensive bids against the few attractive assets. This calls for the generation of more viable investment options in the local real estate sector and the Botswana government has initiated investment regulations for pension funds to invest more capital within the Botswana market by the year 2050.